Tax awareness in the tax collection process in Santa Elena - zoe Elisabeth Estévez-Torres; Juan Eduardo Rocafuerte-González (CLIO América, 2018)
In recent years, tax collection in the province Santa Elena has had a gradual increase, due to proper administration of the collection management by the entity of control —Internal Revenue Service (SRI) — and reforms implemented in recent time. However, the amount raised by the sanctions maintained a rising trend. In addition, is the level of preparedness of citizens in tax matters, which promotes an analysis of training activities that have been offered by the Internal Revenue Service and assert that tax training does not reach the ordinary citizen because the in Situ trainings are held in the main districts of the provinces of Ecuador. The research analyzes the incidence of tax awareness in the collection of taxes in the province of Santa Elena, from a qualitative methodology and a exploratory-descriptive approach, and proposes a methodological guide to train educators on tax issues in partnership with unions of the town, as a strategy to achieve an improvement in decision making about issues encountered in the community and to contribute to the formation and development of public awareness, important training for all those who decide to start a business.